Wild Edible Fruits Used by the Tribal Communities of Rowangchhari Upazila in Bandarban Hill District, Bangladesh: Edible Fruits Used by the Tribal Communities of Rowangchhari (Bangladesh Journal of Agriculture, 2024)
Wild edible fruits play a vital role in the daily lives of the ethnic people living in Chittagong Hill Tracts. Fruits help in a healthy lifestyle as the main source of minerals and vitamins. It also has great socio-economic significance for medicinal values. The present study deals with the identification, documentation, and exploration of wild edible fruits consumed by tribal communities in the Rowangchhari upazila of Bandarban Hill District, Bangladesh. Information on wild edible fruit tree species was collected through structured and semi-structured interviews. A total of 35 wild edible fruits belonging to 23 families were recorded with their scientific name, family, local name, time of availability, and mode of consumption. These fruits were generally eaten fresh and raw. Dillenia indica, Diospyros malabarica, Ficus racemosa, Flacourtia jangomas, Haematocarpus validus, and Syzygium fruticosum are some fruits that are commonly used by the local inhabitants, and some of these fruits are also used to treat different diseases through traditional methods.Bangladesh J. Agri. 2024, 49(1): 86-94